Building Competitive Green Industries : The Climate and Clean Technology Opportunity for Developing Countries - World Bank Group (Washington, DC, 2014)
Climate change will have its largest impacts on developing countries, with poor populations particularly hard hit and unable to adequately adapt. There is an opportunity for developing countries to pursue a complementary approach, emphasizing building up the capabilities of local firms to participate in the business opportunities surrounding climate change. Climate change therefore represents an opportunity for developing countries to build local green industries that can drive sustainable economic growth and provide environmental benefits. This report offers insight to policy makers and other stakeholders seeking to develop competitive green industries in developing countries. It provides an overview and estimate of the market opportunity for climate and clean technology business in developing countries over the coming decade. It identifies which aspects of these markets are most accessible to local firms and to small and medium enterprises (SMEs) in particular. Using a newly gathered set of firm data, it identifies which parts of the value chain are already being targeted by local industry. Finally, it provides a set of actions that can be considered for countries that intend to build up local green industries.